The Kyrgyz Republic : Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report ;, 2014)
This Poverty Reduction Strategy Paper on Kyrgyz Republic highlights that the period 2009 through filled with symbolic events marked a new milestone in the Kyrgyz Republic development and will enter the country's history as the period of strength test for the Kyrgyz statehood and entire public administration system including socio-political, economic, environmental, financial and other areas of development management. The country development background during that period included the world financial crisis and growing uncertainty on world markets which created risks for all market actors including the Kyrgyzstan's key trade partners such as Russia, Kazakhstan, and China. The government officially declared the country's sustainable development-oriented policy. For Kyrgyzstan as a country with its still high poverty level, particularly in rural areas, and limited natural and financial resources, the sustainable development policy seems today's logically and politically justified choice. The sustainable development model itself suggests striving for systemic, comprehensiveness, and balance in development. Transition to sustainable development suggests considering economic growth through the prism of human values and reasonable use of natural resources.